Adsorption of Remazol Brilliant Blue R Using Amino-Functionalized Organosilane in Aqueous Solution - Ozi Adi Saputra; Alifia Harista Rachma; Desi Suci Handayani (Universitas Gadjah Mada, 2017)
Synthesis of amino functionalized organosilane (AFOS) via UV-irradiation method has been conducted. In this research, the precursors for synthesizing AFOS are 3-glycydiloxypropyl trimethoxysilane (GPTMS) and ethylene diamine. Synthesis of amino functionalized organosilane was performed for 16 h monitored by Infra-red spectroscopy technique. The morphological structure of AFOS was observed by scanning electron microscopy. The adsorption process was conducted in the batch method using Remazol Brilliant Blue R (RBBR) as anionic dye model. In this study, the pH, contact time and dyes concentration were varied to determine the optimum pH, kinetic and isotherm adsorption. Based on the calculation, the kinetic rate of the RBBR adsorbed onto AFOS was determined by k2 (pseudo second-order). Moreover, the isotherm study showed that the Langmuir model fitted for the adsorption of RBBR onto AFOS with Qm by 21.3 mg g-1.